(untitled) (Comparative & International Education Series, 2021)
This study, as a segment of a longitudinal study, explores the social and educational trajectories of ‘students of the new global elite.’ The data gathered through interviews, personal narratives, diaries and field observations were used as evidence for contestation and negotiation of many facets of the participants’ elite status, distinction, and privilege in a global university contact zone. The intersubjective nature of their identity negotiations was located discursively with its symbolical and historical dimensions. The analysis of social class in relation to language learning revealed that participants had to negotiate between the two opposite positionings: the oppressed outsider and the privileged insider. Theirs was a clash of two historical class positionings, in other words, two habituses. How language learning as an agentive act reproduces or challenges the social structure is of particular interest.